Maternal mental health matters: Indicators for perinatal mental health—A scoping review - Elly Layton; Alexandra Roddy Mitchell; Elissa Kennedy; Allisyn C. Moran; Francesca Palestra; Neerja Chowdhary; Shanon McNab; Caroline S. E. Homer (PLoS ONE, 2025)
Perinatal mental health disorders are a significant contributor to morbidity and mortality in childbearing women. The World Health Organization recommends all women be screened for mental health disorders postnatally and have diagnostic and management services available. There are, however, currently no global indicators in use which measure the status and progress of perinatal mental health. The aim of this scoping review was to identify existing perinatal mental health indicators and propose a core set which could be used at a global level. We used the Global Perinatal Mental Health Theory of Change as the conceptual framework. We found 25 indicators for PMH aligned with the Global Perinatal Mental Health Theory of Change, which were condensed to form a core set of nine indicators These core indicators include the proportion of women with depression, anxiety, post-traumatic stress disorder, psychosis, or adjustment disorders in the perinatal period; the proportion of women screened for these services; the proportion who have access to services following a positive diagnosis; and, the proportion of healthcare providers trained to provide mental health care. This review forms part of the foundational work for the development of a global monitoring framework which would be able to monitor progress towards the provision of universal high quality perinatal mental health care.